Carfilzomib or bortezomib in relapsed or refractory multiple myeloma (ENDEAVOR): an interim overall survival analysis of an open-label, randomised, phase 3 trial. Issue 10 (October 2017) - Dimopoulos, Meletios A; Goldschmidt, Hartmut; Niesvizky, Ruben; Joshua, Douglas; Chng, Wee-Joo; Oriol, Albert; Orlowski, Robert Z; Ludwig, Heinz; Facon, Thierry; Hajek, Roman; Weisel, Katja; Hungria, Vania; et al.
Summary: Background: The phase 3 ENDEAVOR trial was a head-to-head comparison of two proteasome inhibitors in patients with relapsed or refractory multiple myeloma. Progression-free survival was previously reported to be significantly longer with carfilzomib administered in combination with dexamethasone than with bortezomib and dexamethasone in an interim analysis. The aim of this second interim analysis was to compare overall survival between the two treatment groups. Methods: ENDEAVOR was a phase 3, open-label, randomised controlled trial in patients with relapsed or refractory multiple myeloma. Patients were recruited from 198 hospitals and outpatient clinics in 27 countries in Europe, North America, South America, and the Asia-Pacific region. Patients were aged 18 years or older, had relapsed or refractory multiple myeloma, and had received between one and three previous lines of therapy. Patients were randomly assigned (1:1) to receive carfilzomib and dexamethasone (carfilzomib group) or bortezomib and dexamethasone (bortezomib group) through a blocked randomisation scheme (block size of four), stratified by International Staging System stage, previous lines of treatment, previous proteasome inhibitor therapy, and planned route of bortezomib delivery if assigned to the bortezomib group. Carfilzomib (20 mg/m 2 on days 1 and 2 of cycle 1; 56 mg/m 2 thereafter) was given as a 30-min intravenous infusion on days 1, 2, 8, 9, 15, and 16 of 28-day cycles; bortezomib (1·3 mg/m 2 ) was given as an intravenous bolus or subcutaneous injection on days 1, 4, 8, and 11 of 21-day cycles. Dexamethasone (20 mg oral or intravenous infusion) was given on days 1, 2, 8, 9, 15, 16, 22, and 23 in the carfilzomib group and on days 1, 2, 4, 5, 8, 9, 11, and 12 in the bortezomib group. The primary endpoint of ENDEAVOR, progression-free survival, has been previously reported. A stratified log-rank test was used to compare overall survival between treatment groups for this prospectively planned second interim analysis. Efficacy assessments were done in all randomly assigned patients (the intention-to-treat population) and the safety analysis included patients who received at least one dose of study treatment. This trial is registered withClinicalTrials.gov, numberNCT01568866, and is no longer enrolling patients. Findings: Between June 20, 2012, and June 30, 2014, 1096 patients were assessed for eligibility, of whom 929 were randomly assigned (464 to the carfilzomib group and 465 to the bortezomib group). The cutoff date for this prespecified interim analysis was Jan 3, 2017. Median overall survival was 47·6 months (95% CI 42·5–not evaluable) in the carfilzomib group versus 40·0 months (32·6–42·3) in the bortezomib group (hazard ratio 0·791 [95% CI 0·648–0·964], one-sided p=0·010). Grade 3 or worse adverse events were reported in 377 (81%) of 463 patients in the carfilzomib group and 324 (71%) of 456 patients in the bortezomib group, and serious adverse events in 273 (59%) patients in the carfilzomib group and 182 (40%) in the bortezomib group. The most frequent grade 3 or worse adverse events were anaemia (76 [16%] of 463 patients in the carfilzomib group vs 46 [10%] of 456 patients in the bortezomib group), hypertension (67 [15%] vs 15 [3%]), pneumonia (42 [9%] vs 39 [9%]), thrombocytopenia (41 [9%] vs 43 [9%]), fatigue (31 [7%] vs 35 [8%]), dyspnoea (29 [6%] vs ten [2%]), decreased lymphocyte count (29 [6%] vs nine [2%]), diarrhoea (18 [4%] vs 39 [9%]), and peripheral neuropathy (six [1%] vs 28 [6%]). Treatment-related deaths occurred in five (1%) of 463 patients in the carfilzomib group (pneumonia [n=2], interstitial lung disease [n=1], septic shock [n=1], and unknown [n=1]) and two (<1%) of 456 patients in the bortezomib group (cardiac arrest [n=1] and pneumonia [n=1]). Interpretation: Carfilzomib provided a significant and clinically meaningful reduction in the risk of death compared with bortezomib. To our knowledge, carfilzomib is the first and only multiple myeloma treatment that extends overall survival in the relapsed setting over the current standard of care. This study is informative for deciding which proteasome inhibitor to use for treating this disease. Funding: Onyx Pharmaceuticals Inc, an Amgen Inc subsidiary.